Communication tools for distance learning students - Cossa, Adele (Department of Computer Science, 2021)
In distance learning, ICT tools are used to bridge the instructional gap caused by physical distance between the lecturer and the student. Therefore, more effective communication tools can help to enhance the success of a distance learning curriculum. Communication barriers such as disconnectedness, conceptual confusion and lack of social pressure to perform, can negatively affect the success of distance learning. Careful design and implementation of contextually appropriate communication tools is vital in a distance learning curriculum. The University of Cape Town (UCT) Conversion Masters in Information Technology (MIT) originally used a tool called Vula for communication between staff and students, as well as student-to-student communication. Vula is UCT's implementation of the Sakai learning management system. Between 2016 and 2018, a major shift was observed in the adoption and use of communication tools within the programme. There was a noticeable decrease in dialogue between students and lecturers on Vula, and an increase in student-to-student communication using WhatsApp. In 2018, the Slack communication tool wasintroduced to the MIT degree with the objective of increasing communication and collaboration between students and lecturers. This study investigates the adoption and use of the three communication tools (Vula, WhatsApp and Slack) within the context of the University of Cape Town MIT programme. The research aims to provide an understanding of communication needs and practice that can inform the design of distance learning programmes and enable them to harness the potential of social communication tool features. The study describes the nature of communication within the UCT MIT degree. The research also explores the functional features of the tools and how they are used, and the frequency of interaction on the various communication platforms within the MIT programme. This is complemented by a survey of current MIT students and their perceptions. The research analysed 2605 communication messages in Vula (UCT's name for the Sakai learning management system), Slack and WhatsApp communication tools over the three-year transition period 2016-2018. Feedback from a student survey, in which 11 respondents completed a questionnaire after an interview, is also presented. Based on questionnaire responses from MIT students, Vula is viewed as the best tool for administrative matters, WhatsApp is preferred for sharing information and checking on peers, and Slack is perceived as best for communication with all types of participants - students, lecturers and tutors. Most respondents rated WhatsApp as accessible, convenient and providing a good experience, while far fewer did so for Vula and Slack. WhatsApp was also seen to be the tool students used to reinforce or follow up on communications posted on the other tools.